# `(8x)/3 - (x-1)/4 = (x+15)/6`

### 1 Answer | Add Yours

We want to solve for x in the following:

`(8x)/3 - (x-1)/4 = (x+15)/6`

Usually, it's easier to get rid of the denominators first. We have to look for the least common denominator of the fractions. In this case, the LCD is 12. Hence:

`(32x)/12 - (3x-3)/12 = (2x + 30)/12`

`(32x - 3x + 3)/12 = (2x+30)/12`

`32x - 3x + 3 = 2x + 30`

`29x + 3 = 2x + 30`

`29x - 2x = 30 - 3`

`27x = 27`

`x = 1`

Hence, x=1.

[Check:

`(8*1)/3 - (1-1)/4 = (1+15)/6`

`8/3 - 0 = 16/6`

`8/3 = 8/3` ]

` `